Sistem Informasi Penerimaan Murid Baru Berbasis Web Menggunakan Metode Waterfall - Aldi, Febri (Sinkron : jurnal dan penelitian teknik informatika, 2021)
The current development of information technology on the activities of people's daily lives is very influential. Where in doing an activity that takes a lot of time can be shortened to complete it. One of the things that we can see at this time is in the field of education. Education service technology is feasible if the government, education service providers, and the community all work together. The problem is how to build information system technology that can provide educational service processes without intervening in existing operational standards. The New Student Admissions Information System is a website-based platform designed to enable public access to information about schools and the new student registration process. The waterfall approach was used to construct this information system, together with the PHP programming language, the Codeigniter 3 framework, the MVC pattern, and the MySQL database. The results obtained in the form of a new student admission information system website that provides services related to registration, and processing of registration data by the school administration. With this research, it is expected to facilitate new student admission officers at Al Azhar Islamic Elementary School 32 Padang to process data well, and help parents to register their children as new students at Al Azhar Islamic Elementary School 32 Padang.